ANALISIS GAS BUANG KENDARAAN BERMOTOR RODA EMPAT DI KOTA MAKASSAR - Rauf, Syafruddin; Aboe, Akhmad Faisal; Ishak, Indrian Tesukandar (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Along with the increasing needs of the community, then the transport activities is also increasing. Lead to high levels of pollutants due to emissions of smoke (release) of the motor vehicle. The main pollutants resulting from motor vehicle exhaust emissions are carbon dioxide (CO2), nitrogen oxides (NOX), carbon monoxide (CO) and hydrocarbons (HC). The intent of this study is to construct a model of the motor vehicle emission control in Makassar city and become a referral for the Government in making policies for controlling air pollution. And with data retrieval from a third point in the city of Makassar, conducted by the Office of the BLHD, i.e. the Urip Sumohardjo, road Street, and the Boulevard Jendral Sudirman, then proceed with analyzing the data with categorizing the characteristics of each, and then calculate the volume of traffic, then calculate the graduation test emissions rating, and analyzing the value of the equation regresinya.